Sleep, Diet, Physical Activity, and Stress during the COVID-19 Pandemic: A Qualitative Analysis - Kyanna Orr; Zachary Ta; Kimberley Shoaf; Tanya M. Halliday; Selene Tobin; Kelly Glazer Baron (Behavioral Sciences, 2022)
The COVID-19 pandemic has changed routines and habits, raising stress and anxiety levels of individuals worldwide. The goal of this qualitative study was to advance the understanding of how pandemic-related changes affected sleep, diet, physical activity (PA), and stress among adults. We conducted semi-structured, qualitative interviews with 185 participants and selected 33 interviews from a represented sample based on age, race, and gender for coding and analysis of themes. After coding for thematic analysis, results demonstrated four primary themes: sleep, diet, PA, and stress. Sleep sub-themes such as poorer sleep quality were reported by 36% of our participants, and 12% reported increased an frequency of vivid dreams and nightmares. PA was decreased in 52% of our participants, while 33% experienced an increase and 15% experienced no change in PA. Participants also reported having an improved diet, mostly among women. Stress was elevated in 79% of our participants and was more likely to be discussed by women. Many participants reported how stress was involved in precipitating health behavior change, especially for sleep. Increased stress was also linked to elevated anxiety and depression among participants. The results of this qualitative study demonstrate how managing stress could have a beneficial effect on promoting health behaviors and mental health during the COVID-19 pandemic and beyond.